General chemistry - Yambao, Bernadette A.; Geronimo, Marites C.; Zabala, Arlene A. (Valenzuela City Mutya Pub. House, 2006)
"Chemistry Laboratory Experiments were written for students of General Chemistry I and II. This is a revised chemistry laboratory manual bearing additional experiments for new chemistry students." on Preface.
Keywords: Chemistry -- Study and teaching (Higher) -- Philippines; Chemistry -- Laboratory manuals; Chemistry -- Experiments